Analysis of the Capital Structure of Banks with Islamic Branches in Algeria. The Case Study of Gulf Bank Algeria (AGB) - Bensaad, Abderrahmane; Benbaibeche, Selamne; Bensaad, Yamina (Analiza struktury kapitałowej banków z oddziałami islamskimi w Algierii. Studium przypadku Gulf Bank Algeria (AGB), 2024)
Aim: This study aims to analyze the impact of Islamic banking services on the capital structure of Gulf Bank Algeria (AGB), the first traditional bank in Algeria to offer Islamic financial products since 2008. Methodology: A multiple linear regression model is applied to examine the relationship between Islamic banking windows and key capital structure ratios, including debt-to-equity (DTE) and equity-to-total-assets (ETA). Additionally, the study assesses the influence of profitability metrics (ROA, ROE) and credit risk (CR) on these ratios. Findings: The findings indicate that Islamic windows have a positive impact on the DTE and ETA ratios of AGB. However, no significant relationship is found between profitability indicators (ROA, ROE) or credit risk (CR) and the bank’s capital structure. Implications: The study suggests that Islamic financial products can enhance financial inclusion in Algeria while maintaining manageable risk levels. For instance, murabaha can facilitate credit access for lower--income households, while mudaraba can support SME financing. Further diversification of Islamic financial products is recommended to align with international best practices. Originality/value: This research provides a unique insight into the capital structure of an Algerian bank offering Islamic banking services. Given the limited availability of data in this field, the study contri-butes valuable empirical evidence to the discourse on Islamic finance and its role in financial inclusion.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 2, s. 36-50
Keywords: islamic windows; capital structure; return; risk; Gulf Bank Algeria; okna islamskie; struktura kapitałowa; zwrot; ryzyko